Full Lignin-Derived Electrospun Carbon Materials as Electrodes for Supercapacitors - Thielke, Michael W.; Lopez Guzman, Stiven; Victoria Tafoya, Jorge Pavel; García Tamayo, Esteban; Castro Herazo, Cristina Isabel; Hosseinaei, Omid; Sobrido, Ana Jorge (Frontiers in Materials, 2022)
In the search for more sustainable energy storage devices, biomass-derived materials have been widely researched as carbon source for electrode applications. Here we present the processing of high molecular lignin, an abundant carbon rich biopolymer and byproduct of the pulp and paper industry, into freestanding nonwoven carbon fiber (CNFs) electrodes by using electrospinning. It is worth mentioning that no petrol-derived polymers that are usually included in the electrospinning of lignin, were employed in this work, making these electrodes more sustainable that common lignin-derived carbon electrodes. The effect of the carbonization temperature and oxygen plasma treatment in the electrochemical performance of the CNFs as electrodes for supercapacitors was studied. The upscaling of the processing of lignin into carbon electrodes was also explored by comparing a standard electrospinning set up with a needleless electrospinning equipment that enabled faster and higher throughput. The electrochemical performance of the CNFs increased after plasma treatment of the surface and the electrodes prepared using the standard set up exhibited the highest activity, achieving specific capacitances of up to 103.6 F g-1.